Find the smallest positive value of the nonnegative number λ such that the inequality 2 a + b ≥ λ a b + ( 1 − λ ) 2 a 2 + b 2 holds for all positive real numbers a , b .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
What if we consider n variables? n a 1 + a 2 + ⋯ + a n ≥ λ n a 1 a 2 ⋯ a n + ( 1 − λ ) n a 1 2 + a 2 2 + ⋯ + a n 2
Very cool elementary inequalities problem!
We claim that λ = 0 . 5 is the smallest possible value. This is easily verifiable to work, as follows:
2 a + b a + b ≥ ? 2 1 ( a b + 2 a 2 + b 2 ) ≥ ? a b + 2 a 2 + b 2
But this is true by RMS-AM:
2 a b 2 + 2 a 2 + b 2 2 2 a b + 2 a 2 + b 2 2 2 ( a 2 + 2 a b + b 2 ) ( 2 a + b ) 2 a + b ≥ 2 a b + 2 a 2 + b 2 ≥ 2 a b + 2 a 2 + b 2 ≥ 2 a b + 2 a 2 + b 2 ≥ 2 a b + 2 a 2 + b 2 ≥ a b + 2 a 2 + b 2 ■
Now we must show that any smaller λ will not work. Note that the equation is AM ≥ λ ( GM ) + ( 1 − λ ) ( RMS ) . It is known that AM ≥ GM , and RMS ≥ AM . So for any smaller λ , the pair a = 1 and b = x → 0 lim 1 + x will not satisfy the inequality for sufficiently small x for each constant λ . This can be verified through direct computation.
(x-y)²>=0
=> (x+y)²+(x-y)²>=(x+y)²
=>2(x²+y²)>=(x+y)²
=>
2
x
²
+
y
²
>=
4
(
x
+
y
)
²
=>
2
x
²
+
y
²
>=
2
x
+
y
Put x=
2
a
²
+
b
²
,y=
a
b
and we have our result.
Notice that we can write λ ⩾ 2 a 2 + b 2 − a b 2 a 2 + b 2 − 2 a + b = 2 1 ⋅ 2 a 2 + b 2 + 2 a + b 2 a 2 + b 2 + a b setting a = b = 1 , we get λ ⩾ 2 1 . When λ = 2 1 , it's just QM-AM Inequality. ■
Problem Loading...
Note Loading...
Set Loading...
Since the inequality is homogeneous of degree 2 , we can assume without loss of generality that a 2 + b 2 = 2 , and therefore we can write a = 2 cos θ and b = 2 sin θ for 0 ≤ θ ≤ 2 1 π . Thus we require 2 1 ( cos θ + sin θ ) λ ( 1 − sin 2 θ ) ≥ λ 2 sin θ cos θ + 1 − λ ≥ 1 − cos ( θ − 4 1 π ) for 0 ≤ θ ≤ 2 1 π . Putting φ = θ − 4 1 π , we need λ ( 1 − cos 2 φ ) λ ≥ 1 − cos φ ≥ 1 − cos 2 φ 1 − cos φ = 1 − cos 2 φ ( 1 − cos φ ) ( 1 + cos 2 φ ) = 4 cos 2 2 1 φ 1 + cos 2 φ for − 4 1 π ≤ φ = θ − 4 1 π ≤ 4 1 π . Putting c = cos φ we require λ ≥ F ( c ) = 2 ( c + 1 ) 1 + 2 c 2 − 1 2 1 ≤ c ≤ 1 Now F ′ ( c ) = ( c + 1 ) 2 c 2 − 1 c − 2 ( c + 1 ) 2 1 + 2 c 2 − 1 = 2 ( c + 1 ) 2 2 c 2 − 1 1 [ 2 c ( c + 1 ) − 2 c 2 − 1 ( 1 + 2 c 2 − 1 ) ] = 2 ( c + 1 ) 2 2 c 2 − 1 1 + 2 c − 2 c 2 − 1 is positive for 2 1 ≤ c ≤ 1 , and hence the maximum value of F ( c ) is F ( 1 ) . Thus the least possible value of λ is F ( 1 ) = 2 1 .